2020
DOI: 10.3390/ijerph17093176
|View full text |Cite
|
Sign up to set email alerts
|

How Big Data and Artificial Intelligence Can Help Better Manage the COVID-19 Pandemic

Abstract: SARS-CoV2 is a novel coronavirus, responsible for the COVID-19 pandemic declared by the World Health Organization. Thanks to the latest advancements in the field of molecular and computational techniques and information and communication technologies (ICTs), artificial intelligence (AI) and Big Data can help in handling the huge, unprecedented amount of data derived from public health surveillance, real-time epidemic outbreaks monitoring, trend now-casting/forecasting, regular situation briefing and updating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
193
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(224 citation statements)
references
References 27 publications
1
193
0
1
Order By: Relevance
“…However, not all hope is lost. One of the most promising tools that can help health experts better curb and control the spread of COVID-19 is AIbased disease surveillance systems [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, not all hope is lost. One of the most promising tools that can help health experts better curb and control the spread of COVID-19 is AIbased disease surveillance systems [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Adding the fact that global health crises can often cause economic fallout and resources constraints, the cost-effective nature of technological solutions increases their potential as candidate solutions for solving various healthcare issues [37,[41][42][43]. Lastly, and perhaps most importantly, the potential for some technological-based solutions, such as arti cial intelligence (AI) powered disease surveillance systems, in identifying infection cases with high accuracy, may be the most desirable quality governments need to effectively control the spread of diseases [44][45][46][47][48][49][50]. AI can be understood as "the theory and development of computer systems able to perform tasks normally requiring human intelligence, such as visual perception ... and decision-making" [51].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pinter et al [ 20 ] have developed a hybrid machine learning approach to forecast COVID-19 cases in Hungary. For extensive study and more details about the forecasting approaches for COVID-19, the interested readers are referred to the work by Bragazzi et al [ 21 ] who review the potentials of applying artificial intelligent and big data based approaches in predicting and managing the COVID-19 Pandemic outbreak. The pitfall of the previous studies is that they have focused on historical data of confirmed COVID-19 cases, while some studies have considered some factors like temperature and patient sex.…”
Section: Introductionmentioning
confidence: 99%